An optimal design of crushing parameters of marine gas hydrate reservoirs in solid fluidization exploitation - Guorong Wang; Rong Huang; Lin Zhong; Leizhen Wang; Shouwei Zhou; Qingyou Liu (Natural Gas Industry B, 2019)
To select reasonable excavating and crushing process parameters and nozzle structure parameters is one of the key factors to realize commercial excavation of marine natural gas hydrate (hereinafter “hydrate” for short) in solid fluidization exploitation. For analyzing the factors influencing jet crushing efficiency of hydrate in actual engineering, nozzle diameter, pump pressure and other parameters were simulated and analyzed in k–ε turbulence model based on the laboratory experiments and the field production test data at Liwan 3 Station in the northern South China Sea with a gas production rate of 120 thousand m3/d as the target of commercial hydrate exploitation. And the following research results were obtained. First, the relationship curves of nozzle diameter, pump pressure and displacement are determined when the critical jet speed for crushing hydrate is 24 m/s. Second, the crushing rate to satisfy the daily hydrate sediment excavation of commercial exploitation is 2.48 m3/min and its corresponding jet crushing diameter is 800 mm. Third, when the nozzle diameter is fixed, other parts in the process will be damaged if jet displacement and pump pressure are increased directly. In conclusion, these selected design parameters for commercially excavating and crushing marine non-diagenetic hydrate by means of solid fluidization are conducive to the optimal design of crushing parameters of hydrate in solid fluidization exploitation. Keywords: Natural gas hydrate, Solid fluidization, Nozzle, Fluent, Water jet, Critical crushing rate, Pump pressure, Displacement, Optimal design